The cost of pride: Why do firms from developing countries bid higher? - Hope, Ole-Kristian; Thomas, Wayne; Vyas, Dushyantkumar (Journal of International Business Studies, 2011)
Using an extensive panel of cross-border M&A transactions between 1990 and 2007, we find that firms from developing countries, compared with those from developed countries, bid higher on average to acquire assets in developed countries. We are interested in why these higher bids occur. We find that bids of firms from developing countries are higher in cases where the transaction displays “national pride” characteristics, where national pride is identified through a manual examination of media articles. These results, which are robust to numerous specifications (including alternative measures of national pride) and control variables, are both statistically and economically significant, and highlight a source of pride beyond personal hubris that potentially influences corporate decision-makers.